The potential benefit of pseudo high thermal conductivity for laser powder bed fusion additive manufacturing - Huan Ding; Selami Emanet; Yehong Chen; Shengmin Guo (Materials Research Letters, 2023)
This study examined the impact of transient pseudo high thermal conductivity to the fabrication of crack-free parts with Laser Powder-Bed-Fusion (L-PBF) based additive manufacturing (AM) method. Thermal diffusivity and thermal conductivity of L-PBF samples made by mixtures of IN939 alloy and Si powders were investigated. At temperatures above 800°C, the as-fabricated Si-doped IN939 was observed to exhibit an exceptionally high thermal conductivity, which can be attributed to the occurrence of endothermic reactions. This pseudo high thermal conductivity can effectively minimize the thermal stress and offers a potential solution to produce crack-free L-PBF parts for nonweldable alloys.